An Analysis of “Gerakan Literasi Sekolah” (GLS) as Character Education Building Through Language Skills - Nurhayati Siregar; Sutan Botung Hasibuan; Anita Rahman Hrp (Al-Aulad: Journal of Islamic Primary Education, 2023)
The research aims to shape student character education through language skills activities in class IV of SD IT Al-Izzah Sibuhuan. Data analysis techniques use observation, interviews and documentation. Observations are carried out by observing and recording children's learning activities during learning.In an interview where the interviewer asks directly about an object that is being researched and has been previously designed. This documentation data is used to complement the data obtained from observations and interview.The data sources in this research are the principal and all teachers who teach in class IV at SD IT Al-Izzah Sibuhuan. Implementing the school literacy movement, students read books every day before starting lessons, students pay attention to language skills to improve students' abilities.The results of research by reading students are able to shape their character by exploring the lessons or wisdom they get from reading, so that they can form a character with good character. By writing, students are able to express good and polite words, so that they can form a more creative and communicative character.By listening, students are able to listen well, be responsive, so they can shape students' character for the better. The student character that will be formed through school literacy movement activities is that they like to read and become better and more religious characters